PEMBINAAN PENDIDIKAN DAYAH MELALUI KEGIATAN PELATIHANLIFE SKILL SANTRIWAN DAN SANTRIWATI KABUPATEN ACEH TENGAH - Kausara Usman (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Dayah is the oldest Islamic educational institution in Indonesia, allegedly as an education system that was born and grew through Indonesian culture that is "ingenious" which some people believe has adopted the previous educational model, namely from Hindu and Buddhist education before the arrival of Islam. However, after Islam entered Indonesia, Dayah-Dayah was a place to study Islamic religious knowledge. And people who study Islamic religious sciences in Dayah-Dayah are usually referred to as santri and santriwan. Whereas teachers who teach Islamic religious sciences in Dayah-Dayah are known as Tengku. According to its origin, the word Tengku in the Acehnese language is used for three different types of titles: 1. As an honorary title for items that are considered sacred. 2. An honorary title for old people in general. 3. A title given by the community to an Islamic scholar who owns or becomes a Dayah leader and teaches Islamic classics to his students. The form of this research is qualitative descriptive, namely descriptive qualitative research is research that is included in the type of qualitative research. The purpose of this research is to reveal the facts, circumstances, phenomena, variables and conditions that occur when the research is running and present it as it is. Qualitative descriptive research interprets and tells data related to the situation that is currently happening, attitudes and views that occur in society, conflicts of 2 or more circumstances, relationships between variables, differences between facts, influence on a condition, and others.